Food-Induced Anaphylaxis: Role of Hidden Allergens and Cofactors - Skypala, Isabel J. (Frontiers in Immunology, 2019)
Food anaphylaxis is on the increase, with those who have an allergy to peanuts, tree nuts, milk and seafood at the highest risk of developing such a reaction. However, the diet in many societies is increasingly varied, much of the food consumed is prepared outside the home, and meals are often composed of many different ingredients. Anaphylaxis may occur to a composite food, and it may be unclear whether the reaction is due to contamination or to a culprit allergen present in an added ingredient. Composite foods can contain many allergic proteins present in small amounts, which do not always have to be labelled, unless they feature in European or US labelling regulations. These ‘hidden’ allergens include mustard, celery, spices, lupine, pea, natural food colourings and preservatives, but can occasionally include allergenic material from contaminants such as cereal mites. Hidden allergens can provoke severe reactions to seemingly unconnected foods which might then lead it a diagnosis of idiopathic anaphylaxis. The same problem can arise with two well-known types of food allergy; wheat-dependant exercise induced anaphylaxis and allergy to non-specific Lipid Transfer Protein allergens, both of which might only manifest when linked to a cofactor such as exercise. Many of these risk factors for food anaphylaxis have a common link; the public’s engagement with popular concepts of health and fitness. This includes the development of a food and exercise culture involving the promotion and marketing of foods for their health-giving properties i.e. meat substitutes, wheat substitutes, supplements and alternative or ‘natural‘ remedies for common ailments. Some of these foods have been reported as the cause of severe allergic reactions, but because they are often viewed as benign unlikely causes of severe allergic reactions, could be considered to be hidden allergens. The best resource to elicit the likelihood of a hidden allergen provoking an allergic reaction is to take a detailed history of the allergic reaction, presence of co-factors, foods suspected, type of food and where it was consumed. A good knowledge of commonly used ingredients, and list of potential hidden allergen suspects are essential tools for the food allergy detective.